Strategic academic leadership and high-tech economic growth - Popkova, Elena G.; Sergi, Bruno S. (Frontiers in Education, 2023)
Considering the context of the Fourth Industrial Revolution, higher education must play a significant role in the social-investment model of economic growth. To what extent higher education supports strategic academic leadership and high-tech economic development is still being determined. The article proposes direct actions for improving university management through higher educational and technological functions. We establish the specific directions for university management in neo-industrialization 4.0 to ensure extensive accessibility of higher education and enhance university management efficiency.